Analysis of Groundwater Treatment System for Clean Water in Punggur Besar Village Kubu Raya Regency - Sibuea, Cristin Liony Cindy; Yulianto, Eko; Nirmala, Azwa (Jurnal Teknik Sipil, 2025)
Punggur Besar Village, Kubu Raya Regency, faces challenges in providing clean water due to poor groundwater quality and limited distribution capacity. This study aims to assess water quality, estimate the demand for clean water, and evaluate the production capacity of the existing treatment system. The research involved preliminary surveys, literature reviews, data collection, water quality analysis, and an assessment of production capacity about community needs. The findings reveal that aeration alone is insufficient to meet water quality standards. However, filtration significantly improved groundwater quality, reducing turbidity by 98,2%, total dissolved solids by 17,3%, colour by 98,7%, iron (Fe) by 99,7%, manganese (Mn) by 33,3%, and increasing pH by 26,4%. The quality of river water, both untreated and aerated, remained below acceptable standards. The current production capacity of a single treatment unit, 20.966,40 litres per day, can serve only about 210 residents, far below the village"™s total demand of 829.800 litres per day. Meeting the community"™s needs would require 39 additional units, each powered by 10 solar panels and equipped with a Grundfos SQF 1-70 submersible pump. This study highlights the urgency of expanding water treatment infrastructure and integrating renewable energy technologies to ensure sustainable and equitable access to clean water for all residents of Punggur Besar Village.